HUBUNGAN INTENSITAS OBSERVASI SEKOLAH DAN MOTIVASI BELAJAR DENGAN KOMPETENSI PEDAGOGIK MAHASISWA - Radhea, Radhea; Vincan, Vincan; Wahyu, Wahyu; Arif, Arif; Netriwati, Netriwati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Pedagogical competence is an essential ability that must be possessed by education program students as prospective teachers. Field observations indicate that not all students optimally utilize school observation activities, and there are differences in students’ learning motivation during lectures. This condition is suspected to affect the development of students’ pedagogical competence. This study aims to examine the relationship between the intensity of school observations and learning motivation with students’ pedagogical competence. A quantitative approach was applied using a correlational method. The study involved 43 students as respondents. Data were collected using a Likert-scale questionnaire consisting of 36 items covering three research variables: school observation intensity, learning motivation, and students’ pedagogical competence. Data were analyzed using IBM SPSS Statistics through a series of tests including validity, reliability, normality, correlation, and multiple regression analyses. The study found a positive relationship between school observation intensity and students’ pedagogical competence, as well as a positive association between learning motivation and pedagogical competence. Regression analysis indicated that school observation intensity and learning motivation collectively contributed to students’ pedagogical competence, with a coefficient of determination of 0.547 or 54.7%. These findings suggest that school observation intensity and learning motivation play a significant role in enhancing pedagogical competence among prospective teachers.